Urban Entanglements in Three African Canadian Plays: Lorena Gale’s Angélique, George Boyd’s Consecrated Ground, and Andrew Moodie’s Riot - Tompkins, Joanne (Theatre Research in Canada / Recherches théâtrales au Canada, 2009)
This paper examines the ways in which three African Canadian plays—Andrew Moodie’s Riot, Lorena Gale’s Angélique, and George Boyd’s Consecrated Ground—rehearse moments of racism regarding the African Canadian diaspora. I explore the in/visibility and hyper-visibility of blackness in three plays that are set in a past which connects directly to contemporary politics: Angélique takes place in 1734 Montreal and the present, Consecrated Ground is set in Nova Scotia’s Africville in 1965, and Riot looks back to Toronto in 1992. Yet rather than just documenting points on a visibility continuum, the plays also raise the prospect of establishing alternative—albeit metaphoric—definitions of ‘belonging.’ Using Avtar Brah’s concept of "diaspora space," I argue that by exploring a compromised form of diaspora space as a means of locating African Canadian subjects, the plays provide an abstract alternative to ‘belonging’ in their urban narratives, in the wider community, and the larger nation. The performance of diaspora spaces, even if compromised, helps make visible African Canadian identities, as the plays renegotiate the nature of Canadian landscape, history, and identity at large. Résumé À partir de trois pièces afro-canadiennes—Riot de Andrew Moodie, Angélique de Lorena Gale, et Consecrated Ground de George Boyd—Tomkins examine comment sont représentés les moments de racisme à l’endroit de la diaspora afro-canadienne. De plus, elle explore l’in/visibilité et l’hyper-visibilité de la négritude dans trois pièces qui ont lieu dans le passé à des époques qui sont directement reliées à des enjeux politiques contemporains : l’intrigue d’Angélique se déroule à Montréal en 1734 et au temps présent; Consecrated Ground se passe à Africville, en Nouvelle-Écosse, en 1965; et Riot fait un retour en arrière sur la ville de Toronto, en 1992. Plutôt que documenter des points sur un continuum de la visibilité, les pièces évoquent la possibilité d’établir d’autres définitions—si métaphoriques qu’elles soient—de l’« appartenance ». À partir du concept d’« espace diasporal » que propose Avtar Brah, Tomkins fait valoir qu’en explorant un espace diasporal marqué par le compromis pour situer des personnages afro-canadiens, les pièces fournissent une autre forme d’ « appartenance » aux récits urbains, à une communauté et à une nation. La représentation d’espaces diasporaux, même ceux qui sont marqués par le compromis, rend visible les identités afro-canadiennes alors que les pièces négocient la nature du paysage, de l’histoire et de l’identité canadienne dans son ensemble.